Stratification and Characteristic of Water Masses in Selayar Slope-Southern Makassar Strait - Isnaini Prihatiningsih; Indra Jaya; Agus Saleh Atmadipoera; Rina Zuraida (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2021)
Selayar slope is the confluence of the Indonesian Throughflow (ITF) from the Makassar Strait and seasonal Java-Flores current. The CTD data from Java-Makassar-Flores (JMF) Cruise where an intensive 24-h CTD “yoyo” measurement was conducted in Selayar Slope is used to determine the stratification and characteristic of water masses in the Selayar slope - southern Makassar Strait. The analyses were performed using TS Diagram processed with Matlab and Ocean Data View (ODV). The surface potential density of 24.25 sq with stratification of water masses is dominated by Makassar ITF. The water mass with higher salinity (34.6 psu) is North Pacific Subtropical water (NPSW) and lower salinity (34.44 psu) is North Pacific Intermediate Water (NPIW). However, water mass with density above 24.25 sq caused NPSW to be drastically extracted by less-saline water (34.15 psu) originated from Java Sea, where salinity profiles are more clearly observed between surface density of 22.0 sq and 23.50 sq.. Keyword: stratification and characteristic, water mass, Selayar Slope, JMF Cruise, TS Diagram